Civil society - Edwards, Michael 1957- (Polity Press, 2009)
Is civil society the big idea for the 21st century? Or will the idea prove another false horizon in the search for a better world? By illuminating the uses and abuses of different theories and traditions, this book should help readers of all persuasions to answer this question for themselves.